Assignment of stochastic models for the domain of port terminal operations - Hess, Mirano; Hess, Svjetlana (Transport, 2011)
The paper presents the optimization possibilities of port terminal operations in order to generate maximum gain. Planning these processes is a demanding daily task taken on before dealing with port management, since transhipment operations, cargo loading and dispatching, maintenance and control of transhipment and transportation means are subject to hardly predictable and unexpectable stochastic conditions under which planning optimal terminal operations will include the examination of stochastic processes on the terminal. A model of states and transitions with gain and a model of optimal strategies in terminal management are set up. Furthermore, a model for determining the structure of transhipment equipment is developed. The devised models were adapted to the specificities of a port terminal and tested using the sample of a general cargo terminal.First Published Online: 07 Jul 2011